Ability of Early Literacy Measures to Predict Future State Assessment Performance. (September 2016) - Utchell, Lynn A.; Schmitt, Ara J.; McCallum, Elizabeth; McGoey, Kara E.; Piselli, Kate
The purpose of this study was to determine the extent to which early literacy measures administered in kindergarten and Oral Reading Fluency (ORF) measures administered in Grade 1 are related to and predict future state reading assessment performances up to 7 years later. Results indicated that early literacy and ORF performances were significantly and moderately related to performances in Grades 3, 5, and 7. Grade 3 achievement was best predicted by ORF, followed by Phoneme Segmentation Fluency (PSF), and then Initial Sound Fluency (ISF). After controlling for the effects of previous state assessment scores in Grade 3, additional significant variance in Grade 5 performance was accounted for by ORF. Finally, after controlling for the effects of Grades 5 and 3 state assessment performances, early literacy and ORF measures did not significantly predict Grade 7 achievement. Discussion focuses on the implications of these findings for theory and practice, as well as limitations and directions for future research.